T follicular helper and memory B cells in IgE recall responses - Joshua F.E. Koenig (Allergology International)
IgE antibodies raised against innocuous environmental antigens cause allergic diseases like allergic rhinitis, food allergy, and allergic asthma. While some allergies are often outgrown, others (peanut, shellfish, tree nut) are lifelong in the majority of individuals. Lifelong allergies are the result of persistent production of allergen-specific IgE. However, IgE antibodies and the plasma cells that secrete them tend to be short-lived. Persistent allergen-specific IgE titres are thought to be derived from the continued renewal of IgE plasma cells from memory B cells in response to allergen encounters. The initial generation of allergen-specific IgE is driven by B cell activation by IL-4 producing Tfh cells, but the cellular and molecular mechanisms of the long-term production of IgE are poorly characterized. This review investigates the mechanisms governing IgE production and Tfh activation in the primary and recall responses, towards the objective of identifying molecular targets for therapeutic intervention that durably inactivate the IgE recall response.